The effects of Advanced Glycation End Products (RAGE)-374T/A and Gly82Ser variants and soluble-RAGE levels to obesity in children - Kucukhuseyin, O; Ozgen, T; Karagedik, E H; Cesur, Y; Yilmaz Aydogan, H; Yaylim, I; Ergen, H A (Cellular and Molecular Biology, 2016)
In recent years, studies related to advanced glycation end products (AGE) and their interaction with their receptors (RAGE) have advanced our knowledge of the roles of these molecules in different diseases. However, studies concerning AGE-RAGE interaction in obesity are limited and the results are conflicting. RAGE gene is located on 6p21.3, has several polymorphic sites including -374T/A, a functional polymorphism in the promoter region, and Gly82Ser, present within the ligand-binding domain. In the present study, the determination of possible risks in the development of obesity according to RAGE polymorhisms and plasma levels of RAGE (sRAGE) was aimed. 87 obese and 78 healthy children were included in this study. Genomic DNA was isolated with salting-out procedure. RAGE polymorphisms were analyzed by PCR based techniques. In contrast to Gly82Ser, -374T/A allelic and genotypic frequencies were not different between study groups. Ser(SerSer+GlySer genotype) allele frequency was higher in obese cases than controls (74.20%â†’25.80%,OR:2.573,95%CI:1.789-3.699;pGlySer>GlyGly for HDL-C, and opposite for FT4. Besides, Ser carriers had lower insulin (p=0.038) and homa-IR (p=0.081) levels than GG genotype. sRAGE levels were different between obese and control seperately or in combination with RAGE polymorphisms (pTA>AA for -374T/A and SerSer>GlyGly>GlySer for Gly82Ser. According to our results SerSer genotype could have significant effects on sRAGE levels, and increased sRAGE levels and Gly82Ser polymorphism either combinatorially or seperately increased the propensity towards obesity.